Using Microemulsion as Carrier for Drug Transdermal Delivery: The Effect of Surfactants and Cosurfactants - Lu, I-Ju; Fu, Yaw-Syan; Chang, Wen-Yu; Wu, Pao-Chu (Current Pharmaceutical Design, 2019)
Background: The purpose of this study was to evaluate the effect of types of surfactants and cosurfactants on physicochemical properties and permeability of sumatriptan-loaded microemulsions through rat skin. Methods: Different types of surfactants and cosurfactants were used to prepare drug-loaded microemulsions. The physicochemical characters and permeability parameters of these formulations were measured. Results: The experimental microemulsions with varying components had small droplet size ranging from 24.6 nm to 2568.8 nm, low viscosity ranging from 7.49 to 43.34 cps and significant permeation enhancement ratio ranging from 23.0 to 98.6 when compared to the control group. Conclusion: The composition and proportion of surfactants and cosurfactants were key factors for the physiochemical properties of drug-loaded microemulsions. The cumulative transdermal amount of the microemulsion containing mixture surfactant of Laureth-3/Laureth-23 was higher than that of the microemulsion with a mixture of Tween 80/Span 20. In the selected cosurfactant, diethylene glycol monoethyl ether (DEGMEE) showed highest permeation enhancement. Thermodynamic stability tests revealed that the experimental microemulsion was a stable enough formulation to be considered as a suitable carrier for sumatriptan.
Keywords: microemulsion